Associations between the intake of single and multiple dietary vitamins and depression risk among populations with chronic kidney disease - Yu, Chunli; Liu, Kun; Yao, Weiguo; Tang, Dingzhong (Frontiers in Nutrition, 2025)
BackgroundThe effects of multivitamin exposure on depression among patients with chronic kidney disease (CKD) have not been thoroughly explored. This study aimed to explore the effects of individual vitamin intakes and the joint effect of the intake of multiple vitamins (including vitamins A, B1, B2, B6, B12, C, D, E, and K) on depression risk in participants with CKD.MethodsA total of 3,123 participants with CKD (weighted n = 25,186,480) from the National Health and Nutrition Examination Survey database from 2007 to 2014 were included. Weighted multivariate logistic regression models were utilized to analyze the associations of individual dietary vitamin intakes with depression risk. Additionally, Bayesian kernel machine regression (BKMR) and weighted quantile sum (WQS) regression were performed to evaluate the joint effect of the intake of the nine vitamins on depression risk.ResultsThe overall prevalence of depression was approximately 11.3% in the study participants. In the fully adjusted model, high intakes of vitamin A (OR: 0.54, 95% CI: 0.40–0.74), vitamin B1 (OR: 0.67, 95% CI: 0.48–0.95), vitamin B6 (OR: 0.70, 95% CI: 0.49–0.99), vitamin D (OR: 0.67. 95% CI: 0.48–0.94), and vitamin K (OR: 0.61, 95% CI: 0.44–0.85) were associated with a reduced likelihood of depression. BKMR and WQS regression showed that the joint effect of the intake of the nine dietary vitamins had a significant negative effect on depression, with vitamin A intake being the largest contributor in the two models. Lastly, WQS regression reflected the total mixed exposure effect of the nine vitamins (OR: 0.82, 95% CI: 0.69–0.99).ConclusionHigh intakes of vitamins A, B1, B6, D, and K are associated with low depression risk in patients with CKD. Furthermore, co-exposure to the nine dietary vitamins is a crucial factor contributing to low depression risk in this population.